2020
DOI: 10.3390/polym12030661
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Properties of Partially Transparent Wood under Different Delignification Processes

Abstract: Two common tree species of Betula alnoides (Betula) and New Zealand pine (Pinups radiata D. Don) were selected as the raw materials to prepare for the partially transparent wood (TW) in this study. Although the sample is transparent in a broad sense, it has color and pattern, so it is not absolutely colorless and transparent, and is therefore called partially transparent. For ease of interpretation, the following "partially transparent wood" is referred to as "transparent wood (TW)". The wood template (FW) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 24 publications
(20 reference statements)
0
16
0
Order By: Relevance
“…From the perspective of construction materials, the mechanical properties are equally important 30 . The hierarchical cellular structure of wood leads to unique anisotropic mechanical features.…”
Section: Resultsmentioning
confidence: 99%
“…From the perspective of construction materials, the mechanical properties are equally important 30 . The hierarchical cellular structure of wood leads to unique anisotropic mechanical features.…”
Section: Resultsmentioning
confidence: 99%
“…According to p F/S, the maximum tensile strength of the sample can be calculated (Wu et al, 2020). In this text, S is the product of the h value and the b value in Table 1.…”
Section: Mechanical Property Analysismentioning
confidence: 99%
“…Another interesting topic addressed in this issue is the transparency of wood. Wu et al [42] used the orthogonal test method to find the best way of partly delignifying wood. They concluded that this type of transparent wood retained most of the wood texture and color and had a certain degree of light, which means that it may used as a functional decorative material.…”
mentioning
confidence: 99%